The Perception of Mystical Advertising in Television Among Muslim Community (Study on Advertising of Elastex Paint Version â€œRain-Handlerâ€) - Saputra, Windhi Tia; Intyaswati, Drina; Laura MBP, Ratu (Institut Agama Islam Negeri Madura, 2017)
Television has become an effective medium to educate and provide information to the public but misused television can be a powerful medium to spread negative messages. There are several types of television shows that actually cause concern in the community because of the wrong perception that was captured from the television show. The purpose of this study is to find out how the perceptions of the Muslim community to advertising of Elastex paint products that use a mystical approach to advertising on television. This research uses qualitative research approach with descriptive method. Sampling method using judgment sampling, that is from a Muslim audience. The research data was taken through depth interview technique to 10 selected informants. The viewer's perception of the Elastex paint ad showed that most viewers deplore the existence of a rain-handler that gives the impression of being a savior from the rain in the ad, which should be a savior is the power of God. The model in the Elastex paint ad is quite interesting and credible, only a few spectators perceive that the rain-handler does not fit the real character of the shaman. Overall the ads are good and display a creative form of advertising.Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i2.1385